2016
DOI: 10.1186/s12967-016-0795-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of pure argon for renal transplant preservation in a preclinical pig model of heterotopic autotransplantation

Abstract: BackgroundIn kidney transplantation, the conditions of organ preservation following removal influence function recovery. Current static preservation procedures are generally based on immersion in a cold-storage solution used under atmospheric air (approximately 78 kPa N2, 21 kPa O2, 1 kPa Ar). Research on static cold-preservation solutions has stalled, and modifying the gas composition of the storage medium for improving preservation was considered. Organoprotective strategies successfully used noble gases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
0
27
0
2
Order By: Relevance
“…Although some investigators have shown decreased infarct volumes and improved cardiac and neural function with xenon after cardiac and cerebral IRI in pigs, others were unable to confirm these protective qualities. Furthermore, porcine kidneys have recently been observed to show an improvement with argon but not xenon reconditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some investigators have shown decreased infarct volumes and improved cardiac and neural function with xenon after cardiac and cerebral IRI in pigs, others were unable to confirm these protective qualities. Furthermore, porcine kidneys have recently been observed to show an improvement with argon but not xenon reconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis confirmed that inhalation of xenon attenuated IRI and prolonged survival in rodent models of renal IRI and renal transplantation. Saturation of organ preservation solutions with argon had renoprotective effects in transplant models. However, the results from large‐animal models have been disappointing, stressing the importance of performing well designed large‐animal studies before considering clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…And in addition, the perfusate was saturated with Ar via the gas exchanger to expose both the epithelial and the endothelial side of the alveolar membrane during EVLP. This kind of Ar-saturated perfusion solution has also been tested in experimental kidney perfusion leading to improved graft function after transplantation 1213…”
Section: Discussionmentioning
confidence: 99%
“…During EVLP, ventilating the donor lung prior to transplantation, in normothermic conditions with inhalational therapy is feasible 1617. Also, the perfusion solution on EVLP could be saturated with an Ar mixture, as demonstrated with success in experimental perfusion of kidneys preceding transplantation 1213. Replacing nitrogen (N 2 ) with Ar in the gas mixture for the ventilator and for the gas exchanger in the EVLP system, results in a dual exposure of the pulmonary graft to Ar, on both the endothelial and epithelial sides (“postconditioning”).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, researchers stored porcine kidneys in the preservation solution Celsior, which was saturated with argon or xenon. Argon-Celsior showed promise in renal transplant preservation by improving early functional recovery, graft quality, and survival, in comparison to Xenon-Celsior [30]. …”
Section: General Anesthesiamentioning
confidence: 99%